Desain Sistem Informasi Manajemen Aset Rekam Medis dalam Menunjang Kebutuhan Unit Pelayanan dengan Metode Agile - Nurfalah, Irawati; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
All of the patient service units at the Occupational Health Hospital of West Java Province are affected because the present asset management system in the medical record installation is still based on manually recorded information and then archived. As a result, the data collection for incoming goods, outgoing goods, and stock in the system is inaccurate and not yet well controlled. The purpose of this research is to develop a system for managing assets in medical record installations; it will use Visual Studio 2012 for programming, an Access 2013 database for secure data storage, and a development methodology to make data processing easier for officers. Agile approaches are used by the system. Therefore, the author hopes that this design can help medical record officers in monitoring assets in the medical record installation.